Thymoquinone loaded on chitosan nanoparticles alleviated the consequences of cryptosporidiosis infection in a murine model: Evidence from parasitological, histopathological, immunohistochemical, and immunological studies - Abdelmoneim A. Ali; Eman S. El-Wakil; Al-sayed R. Al-Attar; Mahmoud Fawzy; Aya Samy; Zienab E. Eldin; Wafa Abdullah I. Al-Megrin; John T. Nazeer (PLoS ONE, 2025)
Background Cryptosporidiosis, a parasitic zoonosis caused by the genus Cryptosporidium (C.), currently lacks a vaccine or fully effective treatment. Nitazoxanide (NTZ), the only medication approved by the US Food and Drug Administration for treating cryptosporidiosis, exhibits limited efficacy in immunosuppressed hosts. Thymoquinone (THQ), the active component of Nigella sativa, possesses immunomodulatory, antitumor, hepatoprotective, antioxidant, antimicrobial, and antiprotozoal properties. This study evaluated the therapeutic effects of THQ alone or loaded onto chitosan nanoparticles (CsNPs) against Cryptosporidium parvum infection compared to NTZ. Methods Chitosan nanoparticles were synthesized and characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), zeta potential analysis, and scanning electron microscopy. The cytotoxicity of CsNPs, THQ/CsNPs, and NTZ/CsNPs was evaluated on HT-29 cells. Mice were divided into seven groups to assess treatment efficacy through parasitological analysis of oocyst shedding, histopathological examination of intestinal, hepatic, and splenic tissues, immunohistochemical analysis using cyclin D1 staining of intestinal tissue, and immunological analysis measuring IFN-γ and IL-10 cytokine levels. Additionally, pharmacokinetic profiles of THQ and NTZ in free and nanoparticle-loaded forms were analyzed. Results XRD confirmed changes in peak position, shape, and intensity following the loading of THQ and NTZ into CsNPs. FTIR spectra demonstrated distinct differences in peak patterns between loaded nanoparticles and individual components, confirming successful drug encapsulation. Moreover, cytotoxicity studies showed dose-dependent effects on cell viability, with NTZ/CsNPs exhibiting the highest cytotoxicity. Regarding oocyst shedding reduction, THQ demonstrated greater efficacy than NTZ (77% vs. 54%), which was further enhanced when loaded onto CsNPs (89% for THQ/CsNPs vs. 78% for NTZ/CsNPs). Histopathological analysis revealed the restoration of structural alterations in intestinal, hepatic, and splenic tissues in treated groups. Cyclin D1 immunohistochemical staining showed a significant reduction in immunoreactivity in the THQ/CsNP-treated group compared to other treatments. Furthermore, immune responses were modulated by nanoparticle therapies, with significantly lower IFN-γ levels and higher IL-10 levels in treated groups. Pharmacokinetic analysis demonstrated that CsNP formulations significantly improved drug bioavailability by achieving higher peak plasma concentrations (Cmax), earlier time to peak concentration (Tmax), and prolonged half-life (t1/2) compared to free drugs. Conclusion Thymoquinone demonstrated significant potential as an anti-cryptosporidiosis therapeutic agent, with enhanced efficacy when loaded onto chitosan nanoparticles. Chitosan-based nanoparticle formulations improved the pharmacokinetic profiles of both THQ and NTZ, offering a promising strategy for enhancing drug bioavailability and retention while reducing parasitic burden and modulating immune responses effectively.